“Estrategia basada en proyectos para la enseñanza y aprendizaje del área de Ciencias Naturales” - Ayala Escudero, Fernanda Isabel (2021)
The education changes as society and technology progress. For this reason, the educational factors must adapt to the present for applying a new methodological strategy in order to support the students for reasoning, understanding and arguing. The methodological strategies that the teacher applied did not respond to the realities or the needs of the students. Therefore, it was evidenced that it promotes memorist and repetitive learning. In this sense, the objective of this investigation consisted for proposing the Project- Based Learing strategy, through the methodological guide for the strengthening of teaching-learning in the Sciences subject focused for the students in sixth level from “Ramón Páez” Elementary School, Eloy Alfaro Parish, Latacunga Canton, from Cotopaxi Province. The methodology applied was framed in qualitative investigation due to it describes the reality of the educational fact of the face to face education by the observing a teacher and twenty six students for collecting the information by the use and application of methodological strategies in the Sciences area. The proposal consisted in the design of the methodological guide for strengthening the teaching-learning of Sciences. Finally it based on the results obtained, it concludes that to apply the the Project - Based Learning (PBL) methodological strategy will allow to relate theory with practice, contributing a big way for the improvement of the teaching-learning process.